2015
DOI: 10.1093/infdis/jiv319
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Coagulase inStaphylococcus aureusBiofilm Development Reveals New Therapeutic Possibilities for Device-Related Infections

Abstract: High-level resistance to antimicrobial drugs is a major factor in the pathogenesis of chronic Staphylococcus aureus biofilm-associated, medical device-related infections. Antimicrobial susceptibility analysis revealed that biofilms grown for ≤ 24 hours on biomaterials conditioned with human plasma under venous shear in iron-free cell culture medium were significantly more susceptible to antistaphylococcal antibiotics. Biofilms formed under these physiologically relevant conditions were regulated by SaeRS and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
108
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 49 publications
5
108
1
1
Order By: Relevance
“…We previously reported that vancomycin and rifampin concentrations as low as 1 mg/ml inactivated biofilms formed in this assay; however, vancomycin was less effective versus three-and five-day-old biofilm, and rifampin required increasing concentrations of 4 to 8 mg/ml to inactivate mature biofilm (14). Tigecycline concentrations of Ն128 g/ml inactivated biofilm formed over 24 h, while 4 mg/ml proved effective against more mature biofilms formed over 3 and 5 days (Fig.…”
Section: Planktonic Susceptibility Testingmentioning
confidence: 72%
See 2 more Smart Citations
“…We previously reported that vancomycin and rifampin concentrations as low as 1 mg/ml inactivated biofilms formed in this assay; however, vancomycin was less effective versus three-and five-day-old biofilm, and rifampin required increasing concentrations of 4 to 8 mg/ml to inactivate mature biofilm (14). Tigecycline concentrations of Ն128 g/ml inactivated biofilm formed over 24 h, while 4 mg/ml proved effective against more mature biofilms formed over 3 and 5 days (Fig.…”
Section: Planktonic Susceptibility Testingmentioning
confidence: 72%
“…However, when the environmental growth conditions in the host are considered, such as nutrient availability in vivo and the rapid conditioning of implanted device surfaces by the extracellular proteins fibronectin, fibrinogen, and collagen, the relevance of biofilm mechanisms already elucidated under in vitro conditions must come into question, as they may not be as important as once thought. To address this concern, we employed our recently described in vitro biofilm assay, which more closely mimics the physiological environment that is proposed to exist during the pathogenesis of an S. aureus catheter-related infection involving biofilm mediated by the enzyme coagulase (14). Using this more appropriate assay facilitated a more clinically relevant investigation that examined the effects of a range of commonly used antibiotics and antiseptic agents against a number of reference and clinical staphylococcal isolates (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this conclusion must be interpreted with caution. For instance, under in vitro conditions, the relative impact of sarA versus that of the saePQRS (saeRS) regulatory locus on biofilm formation was recently shown to be dependent on the medium used to carry out the biofilm assay (22). Moreover, mutation of saeRS in the USA300 strain LAC was shown to limit virulence in a murine model of posttraumatic osteomyelitis owing to the increased production of the extracellular protease aureolysin, which results in the decreased accumulation of phenol-soluble modulins (PSMs) that would otherwise promote cytotoxicity for osteoblasts and bone destruction (23).…”
mentioning
confidence: 99%
“…All of the above-mentioned infections occur inside the human body; therefore, host factors play an essential role in their development. Local coagulation induced by S. aureus coagulases promotes bacterial attachment to the surfaces of implants (8)(9)(10). After an initial adhesion phase, bacteria divide, deposit an extracellular matrix, and develop complex threedimensional biofilm structures.…”
mentioning
confidence: 99%